Meteorites, ice, and Antarctica - Cassidy, W. A. (William A.) (Studies in polar research., 2003)
Bill Cassidy has led meteorite recovery expeditions in the Antarctic for fifteen years. His searches have resulted in the collection of thousands of meteorite specimens from the ice. This fascinating story is a first hand account of his field experiences on the US Antarctic Search for Meteorites Project.